Diversifikasi Produk Olahan Ikan Lele (Nugget) di Kecamatan Gunungpati, Kota Semarang, Jawa Tengah sebagai Upaya Pencegahan Stunting - Willy Tirza Eden; Laelatul Husniyah; Aryanti Setyaningsih (BADAN PENERBIT STIEPARI PRESS, 2025)
The potential of catfish resources offers potential for development as a profitable fishery business, improving the economy and nutritional quality of food. Diversification of catfish products through product diversification not only increases benefits and added value, but also increases catfish consumption, which can contribute to stunting reduction. The development of diversified processed catfish products to prevent stunting, through outreach and training, will be conducted to PKK in Kalisegoro Village, Gunungpati District, Semarang City on August 2025. The community service program utilizes both qualitative and quantitative methods. The qualitative method utilizes participatory observation during the education and training process. The quantitative method utilizes questionnaires before and after the outreach and training. The program is implemented in three stages: preparation, implementation, and monitoring and evaluation. The evaluation of the community service program, which involved training in making processed food products using catfish as an ingredient, for members of the Family Welfare Movement (PKK) in Kalisegoro Village, Gunungpati District, shows an increase in knowledge about the importance of consuming fish as a way to prevent stunting, as well as an improvement in skills in processing catfish nuggets from 89% to 99%.